Parameter Optimization of Constant Pressure Grouting Technology for Borehole Sealing with Inorganic Noncondensable Material in Tectonic Coalbed of South China. (4th March 2023) - Pengtao, Zhao; Haiqiao, Wang; Long, Wang; Xinlei, Wang; Hongyu, Ma
Abstract : To solve the problem of a rapid attenuation of gas concentration along with drainage borehole collapse in the tectonic coalbeds of South China, a constant pressure grouting technology with inorganic, noncondensable material was proposed. Firstly, the slurry fluidity, water separation rate, and sealing performance of the inorganic sealing materials were tested under different water-cement ratios. The seepage model of slurry in a layer-through borehole was built with COMSOL Multiphysics simulation software, to explore the scopes of loose circles around drainage roadway and borehole, and to analyze the seepage capacity of the slurry under different grouting pressures. Eventually, the sealing performance of the slurry was investigated in the field. The results showed that the inorganic, noncondensable material with the water-cement ratio of 5 : 1 has a strong fluidity, low water retention, high permeability, and good sealing performance. After the excavations of No.2164 drainage roadway and layer-through borehole, there are obvious stress concentrations both at the shoulder corners of the roadway and at the borehole bottom, and the scope of the loose circle around the roadway is about 6.2 m. The effective seepage radius of the inorganic slurry gradually increases with a rising grouting pressure, and the slurry seepage range in the sandstone section is broader than that in the mudstone section. Adopting the constant pressure grouting technology with the slurry, the average drainage concentration of boreholes in Puxi coal mine is 51.5%, and the average gas flow rate is 0.005 m 3 /min, which are 1.35 times and 1.67 times than those with the cement grouting method.